Pilot randomised controlled trial comparing C-Trac splints with Beta Wrist Braces for the management of carpal tunnel syndrome. (June 2013) - Storey, Philip; Armstrong, Daniel; Dear, Helen; Bradley, Mary; Burke, Frank
Introduction: The C-Trac splint has been designed to mechanically stretch the transverse carpal ligament and is advertised as an alternative to surgical Carpal Tunnel Decompression. The purpose of the study is to compare the effectiveness of the C-Trac splint with standard splinting in mild to moderate idiopathic carpal tunnel syndrome. Methods: This is a pilot parallel randomised controlled trial. Forty-nine patients with clinically and neurophysiologically proven carpal tunnel syndrome were randomised into the two treatment groups, C-Trac and Beta Wrist Brace, and reassessed clinically for one year. Results: Patients were generally satisfied with both splints, but two out of the 24 C-Trac patients developed problematic side effects possibly due to using the splint: De Quervains tenosynovitis and basal joint arthritic pain. There was no clinically relevant or statistically significant difference in the success and failure rates of the two splints by eight weeks, six months or at one year. Three of the 25 C-Trac splints (costing £130 each) used during the one-year study required replacement, compared with eight of the Beta Wrist Braces (costing approximately £10 each). Conclusions: These results suggest that C-Trac splint is not dissimilar in efficacy to a resting Beta Wrist Brace. The reported side effects raise questions as to the wisdom of its unregulated use.